Does Work-Life Balance Predict Job Satisfaction? - Adhikari, Ujjwal; Gyawali, Santosh (Journal of Tikapur Multiple Campus, 2024)
The study aims to identify the relationship between determinants of work-life balance (work flexibility, job design, and leave provision) with job satisfaction of bank employees. To portray the relation between variables, a quantitative approach based on descriptive research design is used with a close-ended, structured questionnaire-based primary data survey among bank employees in the Kapilvastu district. A convenience sampling technique was administered to obtain 154 valid responses. The collected data is procured with EFA and multiple regression analysis. There is a significant effect of work-flexibility and leave provision on job satisfaction while job design has no significant effect. The study proposes a framework for work-life balance and job satisfaction with an extensive literature review and statistical analysis. The result can be generalized for the improved performance of employees and to make a better working environment in the organization.